FORMAL AND CASUAL REGISTER IN CRAZY RICH ASIANS MOVIE: SOCIOLINGUISTICS STUDY - Heryono, Heri; Lestari, Vany Yuni; Amanah, Oktaviyanti Sri Nur; Mellinia, Syifa Aulia; Sangkan, Tania Putri, Vina (CENTRAL ASIA AND THE CAUCASUS, 2022)
The correlation of language, culture and society focuses on how social aspects have influenced the use of language. It is necessary to know the style of language used in social environments as it can determine someone's social identity. The theory used for this research is Sociolinguistics which concerns the relationship between language and the context[1] register as a language item associated with discrete occupational or social groups [2] language use is correlated with social factors. The research entitled “Formal and Casual Register In “Crazy Rich Asians Movie: Sociolinguistics Study” is relevant to the use of language in social life closely related to where and how the environment plays an important role in it. The objective of this study is to investigate the characteristics of formal and casual register and to analyze the most influential social class from the use of formal and casual register that affect the characters. The research using qualitative description method; data collection using observation method through listening and noting techniques taken from characters’ dialogues; data analysis using pragmatics and referential identity method. The results are obtained as follows; the characteristics of formal and casual register are different from the vocabularies; both have different lexical and grammatical functions. In addition, the use of formal and casual register is influenced by the character's social class that is concluded if types of register are specified by some special structural characteristics and social factors.